An Update on Phosphine‐Imidazolin‐2‐Imine Iridium(I) Catalysts for Hydrogen Isotope Exchange. Issue 3 (16th November 2022) - Becker, Daniel; Bockfeld, Dirk; Tamm, Matthias
Abstract: The reaction of the bidentate P, N ligand [2‐(1, 3, 4, 5‐tetramethylimidazolin‐2‐imino)phenyl]di‐ tert‐ butylphosphine (1 ) with [Ir(COD)Cl]2 (COD=1, 5‐cyclooctadiene) followed by addition of sodium tetrakis[3, 5‐bis(trifluoromethyl)phenyl]borate, NaBArF24, or lithium tetrakis(nonafluoro‐ tert ‐butoxy)aluminate, Li[AlOC(CF3 )3 4 ], afforded the complexes [(1 )Ir(COD)][BArF24 ] (2 a ) and [(1 )Ir(COD)][AlOC(CF3 )3 4 ] (2 b ). Exposure of 2 b to one atmosphere of dihydrogen gas afforded the diiridium tetrahydride [(1 )2 Ir2 H4 ][AlOC(CF3 )3 4 ]2 (3 b ). The molecular structures of 2 a, 2 b, and 3 b were determined by single‐crystal X‐ray diffraction analyses. In the latter complex, the positions of the hydrogen atoms in the Ir2 H4 core could be refined freely, which had previously proved impossible for the corresponding complex 3 a containing the BArF24 anion. Since 2 a is an established catalyst for ortho‐ directed hydrogen isotope exchange (HIE), the performance of 2 a and 2 b in deuterium labelling reactions was compared for various substrates, including phenylacetic acid derivates and nitrogen‐containing aromatic compounds. Abstract :